The Influence of Accounting Information System Implementation, Internal Audit, and Human Resource Competence on the Effectiveness of Internal Control (A Case Study at PT. Agrodana Futures) - Putra, Johansyah; Sartika, Dewi (Summa : Journal of Accounting and Tax, 2026)
This study examines the influence of Accounting Information System (AIS) implementation, Internal Audit, and Human Resource (HR) Competence on the Effectiveness of Internal Control at PT Agrodana Futures. The research is prompted by the critical role of internal control in the high-risk futures brokerage industry and the scarcity of studies analyzing the combined effect of these three variables in this context. The central research question is to what extent these factors affect internal control effectiveness. This paper provides a new contribution by simultaneously analyzing the roles of AIS, internal audit, and HR competence within a single integrated model, grounded in Agency Theory and Signaling Theory. Previous studies have generally examined these factors separately or outside the futures brokerage sector. A quantitative survey approach was employed. Data were collected from 40 employees via an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that AIS (β = 0.408; p = 0.022), Internal Audit (β = 0.378; p = 0.010), and HR Competence (β = 0.308; p = 0.000) each have a positive and significant effect. Collectively, they explain 87% of the variance in internal control effectiveness (R² = 0.870). The study concludes that a reliable AIS, an independent internal audit function, and competent human resources are key to strengthening internal control systems. These findings underscore the necessity of a holistic approach to internal governance in high-risk industries like futures trading.